Attrition in MOOC: Lessons Learned from Drop-Out Students - Guetl, Christian; Hernandez Rizzardini, R.; Chang, V.; Morales, M. (Springer, 2014)
Despite the popularity of Massive Open Online Course (MOOC), recent studies have found that completion rates are low with some reported to be significantly lower than 10%. The low retention and completion rates are major concerns for educators and institutions. This paper investigates motivations for enrolling in a MOOC on the topic of ‘e-learning’ and discusses reasons for the attrition rates during the course. A survey of 134 students who had not completed the MOOC reveals that only 22% of the students had intended to complete the MOOC but was unable to due to various factors including academic and personal reasons. A big majority of the students indicated that changes in their job, insufficient time, difficulty with the subject matter and unchallenging activities are some of the reasons for the drop-out.